Effect of Nutrition Education On School Going Children Between Ages 10-12 Years - Arora, Niharika (Academy of Agriculture Journal, 2016)
School going children were educated through presentations about the healthy food choices, importance of physical activity, and nutritious food for staying healthy. Subjects were also informed that the television advertisements, not always give the right information and advertisements should not affect their buying behaviors. Before educating the children their pre knowledge about these topics were tested and after delivering the education post results were recorded.